THE PRACTICE OF DIRECT ZAKAT DISTRIBUTION: A Case Study on Gold Mining in Sawang District, South Aceh Regency - Erni Yusfa (JURISTA: Jurnal Hukum dan Keadilan, 2019)
Zakat is a mandatory tax imposed on all forms of property that have entered the nishab, including sought-after assets and treasures. Zakat is due on sought-after treasures, including gold mines, subsequent to their refining and dissolving processes. Islam advises unequivocally that an authorised zakat amil institution oversee the calculation and distribution of zakat, so that its utilisation adheres to the tenets of Islamic law. Zakat muzakki engaged in gold mining within the Sawang District of South Aceh Regency autonomously compute and allocate their zakat in accordance with their personal convictions. In-person distribution is extended to family members, neighbours, and relatives. Therefore, it is highly regrettable when the allocation of zakat fails to reach the intended recipients. The findings of the study indicate that the gold mine zakat muzakki residing in Sawang District, South Aceh Regency personally allocate their zakat to their families, relatives, and neighbours in a manner consistent with their cultural beliefs and the customs prevalent in their vicinity. Due to their lack of confidence in the zakat amil institutions in their region, the muzakki are uninformed about and do not completely comprehend the zakat provisions. Zakat distribution in a direct manner is not impermissible under Islamic law, provided that no argument exists to the contrary. Zakat beneficiaries are solely obligated to adhere strictly to the guidelines outlined in Surah At-Taubah verse 60 with respect to the eight ashnaf of zakat recipients. Fiqh scholars place significant emphasis on the fact that zakat amil institutions oversee the administration and distribution of zakat, in accordance with the principles and practises of zakat distribution that characterised the era of the Prophet Muhammad and his companions.